2014
DOI: 10.1007/s00360-014-0847-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Na+ uptake, ammonia excretion, and their potential linkage in native Rio Negro tetras (Paracheirodon axelrodi, Hemigrammus rhodostomus, and Moenkhausia diktyota)

Abstract: Mechanisms of Na(+) uptake, ammonia excretion, and their potential linkage were investigated in three characids (cardinal, hemigrammus, moenkhausia tetras), using radiotracer flux techniques to study the unidirectional influx (J in), efflux (J out), and net flux rates (J net) of Na(+) and Cl(-), and the net excretion rate of ammonia (J Amm). The fish were collected directly from the Rio Negro, and studied in their native "blackwater" which is acidic (pH 4.5), ion-poor (Na(+), Cl(-) ~20 µM), and rich in dissolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 56 publications
3
32
0
Order By: Relevance
“…In three acidophilic characids of the Amazon Basin, tested in naturally acidic, DOC‐rich water, Na + uptake appeared dependent on ammonia excretion and the mechanism appeared to be strongly dependent on intracellular carbonic anhydrase and basolateral Na + , K + ATPase in the gill epithelium (Wood et al ., ). In the present study, the activities of both Na + , K + ATPase and v‐type H + , ATPase in the gills of C. macropomum were very similar in all four treatment groups (Table ), suggesting that neither acidic conditions nor the presence of SGC DOC affected these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In three acidophilic characids of the Amazon Basin, tested in naturally acidic, DOC‐rich water, Na + uptake appeared dependent on ammonia excretion and the mechanism appeared to be strongly dependent on intracellular carbonic anhydrase and basolateral Na + , K + ATPase in the gill epithelium (Wood et al ., ). In the present study, the activities of both Na + , K + ATPase and v‐type H + , ATPase in the gills of C. macropomum were very similar in all four treatment groups (Table ), suggesting that neither acidic conditions nor the presence of SGC DOC affected these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In rainbow trout and several tetra species acutely exposed to Ag + , Cl − uptake decreased, as did Na + uptake [113,290]. There was also a decrease in CA activity, which would limit the supply of HCO 3 − for exchange with Cl − .…”
Section: Transporters and Physiology Of Individual Ionsmentioning
confidence: 99%
“…Moreover, it remains to be resolved if this Na + /NH 4 + exchange model is effective in acidic, ion-poor environments, where the external [H + ] and [Na + ] are extremely unfavorable for exchange [62]. Some evidence from fish native to blackwater habitats suggests that these exchanges may be de-coupled, whereby Na + uptake depends on NH 3 excretion, but NH 3 excretion is independent of Na + uptake [15]. For example, Hirata et al [18] found that dace native to blackwater increased somatic NH 3 production (glutamate catalysis) to remediate Na + losses, as well as NHE, CA, NBC, and aquaporin (AQP3) transcription (but not HA), whereas non-adapted dace were not able to maintain plasma [Na + ] or pH.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our procedure captured only one of several dimensions important in adaptation to novel physicochemical environments, including population-level variation, developmental plasticity, and epigenetic effects [e.g., 5,6]. Physiological observation of Negro River fishes has indicated that some species possess higher affinity Na + uptake mechanisms and decoupling of NH 3 excretion from Na + import/H + export [e.g., 15]. In addition, the DOC found in Negro habitats may have unique chelating properties utilized by native fishes to minimize ion loss [78,79], and attempts to recreate this with other DOC sources (including Sigma humic acid) have produced mixed results [26,80,81].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation